Gendering the Renaissance commonwealth - Becker, Anna 1978- (Ideas in context, 2020)
This pioneering and innovative study challenges modern assumptions of what constitutes the political and the public in Renaissance thought. Offering gendered readings of a wide array of fifteenth- and sixteenth-century political thinkers, with a particular focus on the two prime thinkers of the early modern state, Niccol o Machiavelli and Jean Bodin, Anna Becker reconstructs a neglected but important classical tradition in political thought. Exploring how 'the political' was incorporated into a wide array of 'private' or 'apolitical' topics by early modern thinkers, Becker demonstrates how both republican and absolutist thinkers - the two poles which organise early modern political thought - relied on gendered justifications. In doing so, she reveals how the foundations of the modern state were significantly shaped by gendered concerns